(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article presents the results of correlation between the avatar`s content and the individual peculiarities (temperament) of the teenager`s personality. It is determined that the avatar is an electronic visualization of the individual and his relation to himself and the outward things, which reflects the basic psychological properties of the individual. It has been experimentally established that theavatars of the investigatedmembers team’s compliance degree is 90%. Energetic types of temperament (sanguineandcholeric) are successfully identified and fully match the avatar`s contentand the main features in 100% of cases.